How Green HRM Helps to Nurture Green & Innovative Behaviours: A Case of SMEs from Kosovo - Valon Llugaxhiu (Journal of Advanced Research in Social Sciences and Humanities, 2024)
Aim: This study investigates the impact of green human resource management (GHRM) on employee green behavior, and innovative work behavior, with a focus on the moderating role of green creativity and the mediating role of green commitment among the Green SME sector in Kosovo. Organizational Identity Theory and Social Exchange Theory are integrated to provide a comprehensive understanding of the dynamics in the context of the Green SME sector. Methodology: Data were collected from 300 senior managers and SME owners within this sector, employing a cross-sectional approach. The study adopts a quantitative methodology, with Smart PLS used for analysis. The primary statistical method employed to assess the study’s hypotheses was partial least squares-structural equation modeling (PLS-SEM). Findings: The findings reveal significant relationships, highlighting the direct positive influence of GHRM on employee green behavior and innovative work behavior. Furthermore, the study underscores the mediating effect of green commitment and the moderating role of green creativity in shaping these relationships. Implications/Novel Contribution: The implications of these findings are discussed in light of sustainable human resource practices in the Green SME sector. The findings offer valuable insights for policymakers in the Green SME sector, illustrating how green human resource management can play a positive role in fostering employee green behavior. This paper stands out for various reasons. Firstly, it makes a valuable contribution to the broader literature on green human resource management in Kosovo. Secondly, it adds to the limited body of knowledge concerning green human resource management within the specific context of the green SME sector. Thirdly, a distinctive aspect of this study lies in its introduction of innovative work behavior as an outcome resulting from green human resource management, with green commitment serving as a mediating variable in the correlation between green human resource management and both employee green behaviors and innovative work behavior.